PERANCANGAN DAN ANALISIS VIDEO DOKUMENTER VIHARA DI KOTA TANJUNGPINANG MENGGUNAKAN METODE MDLC - Jimmy Pratama; Tomy (JURNAL ILMIAH BETRIK, 2023)
Documentary video is a video that records real events or an event that happened in the past. However, documentary videos are also used to promote something. Religious tourism is a travel activity related to religion, that is tourism activities by visiting places of worship that have advantages such as history, myths and legends that are believed by the community. In the city of Tanjungpinang there is religious tourism, which is Viharas / Buddhist places of worship. There is still a lack of promotional activities for tourist attractions in Tanjungpinang City, either directly or indirectly. This research was conducted by developing a documentary video on the monastery in Tanjungpinang City in order to introduce religious tourism to the wider community. Because with the activity of making video documentaries to introduce the temples in Tanjungpinang City in the tourism sector, of course there will be a good influence on the national economy. This research uses a qualitative approach and the MLDC development model by conducting interviews with 3 temple administrators. The video results that have been designed will be analyzed in the form of a media expert test by 2 multimedia experts, a content expert test by 2 temple administrators using the Gregory formula. In addition, the audience respondent test will also be conducted on 30 people in Tanjungpinang City using google form and analyzed using a Likert scale. The test results on media experts and content experts obtained a validity result of "1.00" namely "Strongly Agree" and the audience response test obtained "90%" results for the documentary video that had been designed.